A Needs Analysis of Using a Pragmatics Approach in Teaching Drama in EFL Contexts - Eripuddin eripuddin; Pipit Rahayu; Azi Nurazima Juhastri (Journal of Applied Linguistics, 2026)
This study investigates the need for integrating a pragmatics approach in teaching drama within an English as a Foreign Language (EFL) context. Employing a qualitative needs analysis design, the research involved 23 sixth-semester students of the English Department selected through purposive sampling. Data were collected using open-ended questionnaires structured around a needs analysis framework encompassing target needs (necessities, lacks, and wants) and learning needs. The data were analyzed through qualitative descriptive analysis to identify patterns related to students’ pragmatic competence and instructional expectations.The findings reveal more specific dimensions of learners’ needs. In terms of necessities, students are required to understand how meaning in drama is constructed through context, including implicature, speech acts, and sociocultural norms, in order to interpret characters’ intentions and perform dialogues appropriately. However, in terms of lacks, the data indicate that many students experience difficulties in interpreting implied meanings, recognizing indirect speech acts, and adjusting language use according to social context, which results in overly literal or mechanically delivered performances. Furthermore, regarding wants, students express a strong preference for more interactive and contextualized learning activities, such as role-play, script analysis focusing on pragmatic elements, and explicit instruction on how language functions in real communicative situations.These findings suggest that drama instruction in EFL contexts requires more explicit integration of pragmatic components, not only as supplementary material but as a core aspect of learning. The study highlights the pedagogical value of pragmatics as a conceptual foundation for enhancing both communicative competence and interpretive skills in drama learning. By positioning pragmatic competence as a central learning objective, this research contributes to the development of learner-centered and contextually grounded drama pedagogy in EFL settings. The findings also provide a more concrete basis for future instructional design and empirical research on pragmatics-based drama teaching. Keywords : Need Analysis; Pragmatics Approach; Teaching Drama